The colonial iron horse : railroads and regional development in the Philippines, 1875-1935 - Corpuz, Arturo G. (Quezon City : University of the Philippine Press, 1999)
Revision of the author's thesis (Ph. D. - - Cornell University, 1989)
Includes bibliographical references (p. 211-242) and index.
Keywords: Railroads -- Philippines -- History; Philippines -- History -- 1872-1898; Philippines -- History -- 1896-1948